The status importance and development of poultry keeping in the Sudan - Desai, D.K. (1962)
Discusses the state of poultry production in the Sudan, briefly describing the main types of indigenous breeds and outlining the experimental and extension & advisory programme of the Department of Animal Production aimed at poultry improvement